Engineering of a Polycaprolactone-Stabilized Alginate Hydrogel for 3D Bioprinting of Patient-Specific Implants enabling Sustained Local Dexamethasone Delivery in Inner Ear Therapy (Transactions on Additive Manufacturing Meets Medicine, 2025)
There is an unfulfilled need for local inner ear therapy to treat hearing disorders. We developed a silicone implant enabling drug diffusion from the middle ear into the inner ear. This implant is precisely tailored to conform to the unique anatomical contours of each patient's round window niche, thereby facilitating controlled diffusion of therapeutic agents into the inner ear. To improve the approach biodegradation of the implant would be beneficial to avoid the potential need of explanting the drug delivery device. Alginate hydrogels, while well-established for their cytocompatibility and biodegradability, are inherently limited by insufficient viscosity and suboptimal mechanical integrity, restricting their applicability in 3D bioprinting. To overcome these deficiencies, we engineered a composite hydrogel system through the incorporation of polycaprolactone particles (PCL) to modifying the printability.  The composite material was 3D printable and compression tests and rheological tests determined the elastic properties of the hydrogel and the structural stability under a certain load.  Investigations into swelling kinetics and morphological stability under simulated physiological conditions substantiated the material's durability and functional integrity within 7 days and subsequent degradation over time. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) revealed a homogeneous microarchitecture conducive to controlled drug diffusion, as corroborated by in vitro release kinetics of dexamethasone quantified through high-performance liquid chromatography (HPLC). Cytotoxicity tests demonstrated biocompatibility, and the dexamethasone-loaded hydrogel elicited anti-inflammatory responses in vitro.The PCL-reinforced alginate hydrogel is a promising platform for the fabrication of personalized, biodegradable, and pharmacologically active implants.
Keywords: hydrogel; drug delivery; 3D printed Implant; alginate; local drug therapy; personalized implant